Efektivitas Guru Menggunakan Media Grafis dalam Meningkatkan Kualitas Pembelajaran di Paud - Hasnawaty Paputungan (Peneliti.net, 2021)
This study aims to improve the quality of learning through teacher effectiveness in using graphic media in PAUD. The subjects of this study were the Early Childhood/Tk Institutions in Tomohon Tengah, which totaled 11 Early Childhood/Tk institutions, with 39 teachers, both civil servants and non-PNS. The results showed that based on observations made using a simple random system. So it can be found that out of the 11 PAUD/Tk. And from several research locations, it can be seen that in teaching and learning activities (KBM) there tends to be more use of self-designed teaching aids than using ready-made media or teaching aids or other learning media that are usually purchased at toy stores and so on. The conclusion from this study is that the teacher's ability to manage appropriate learning will produce good quality learning. The use of graphic media developed based on the themes being taught will make learning more interesting and efficient, so that the use of graphic media in learning can improve the quality of learning